2022
DOI: 10.1038/s41467-022-32288-y
|View full text |Cite
|
Sign up to set email alerts
|

Inferring interiors and structural history of top-shaped asteroids from external properties of asteroid (101955) Bennu

Abstract: Asteroid interiors play a key role in our understanding of asteroid formation and evolution. As no direct interior probing has been done yet, characterisation of asteroids’ interiors relies on interpretations of external properties. Here we show, by numerical simulations, that the top-shaped rubble-pile asteroid (101955) Bennu’s geophysical response to spinup is highly sensitive to its material strength. This allows us to infer Bennu’s interior properties and provide general implications for top-shaped rubble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 70 publications
2
19
0
Order By: Relevance
“…These findings are in alignment with recent theoretical models based on Hayabusa2 and OSIRIS-REx data by Zhang et al (2022), which suggest that rapidly rotating asteroids with primitive compositions are more likely to undergo internal deformation than to form binary systems. Our compilation of taxonomic classes for binary systems and creation of a reference population supports these theoretical predictions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are in alignment with recent theoretical models based on Hayabusa2 and OSIRIS-REx data by Zhang et al (2022), which suggest that rapidly rotating asteroids with primitive compositions are more likely to undergo internal deformation than to form binary systems. Our compilation of taxonomic classes for binary systems and creation of a reference population supports these theoretical predictions.…”
Section: Discussionsupporting
confidence: 90%
“…An observational study by Pajuelo et al (2018) found a deficit of C-type NEA binaries, but agreement for all other types with the general population within a 1σ uncertainty. More recently, simulations of the structural evolution of asteroids such as Ryugu and Bennu, targets of the Hayabusa and OSIRIS-REx missions (Fujiwara et al 2006;Hamilton et al 2019), suggest that dark taxonomic types may, on the contrary, be less likely to form binary systems at high spin rates, as they undergo structural deformation rather than rotational fission under these circumstances (Zhang et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…If the strength of Dimorphos' surface is 10 kPa, then the total mass of the ejecta would be 1 order of magnitude lower, and the ejecta will appear much fainter than our simulation presented here. On the other hand, if the surface of Dimorphos is as weak as Bennu with only ∼1 Pa strength (Zhang et al 2022), then the ejecta mass would be 1 order of magnitude higher, resulting in a much brighter ejecta. In addition, if the surface of Dimorphos is close to strengthless (<a fraction of 1 Pa), then the cratering process could happen in the gravity regime and the mass of ejecta could be 1 to 2 orders of magnitude higher than the nominal case.…”
Section: Discussionmentioning
confidence: 99%
“…Itokawa, for example, was found by Hayabusa to show a considerable amount of heterogeneous regolith, distributed nonuniformly, and exhibiting different mechanical properties resulting from the effects of shock and microfracturing (Fujiwara et al 2006;Tanbakouei et al 2019). Some insights on interior strength may be achieved with asteroid shape assessments (Barnouin et al 2019;Daly et al 2020;Hirabayashi et al 2020), lineament evaluations (Buczkowski et al 2008;Besse et al 2014), and, if present, evidence for other surface process such as mass movements (Walsh et al 2008;Scheeres 2015;Sánchez & Scheeres 2018;Hirabayashi et al 2020;Zhang et al 2022). However, the short duration of the flyby and the resulting limitation on surface coverage could hinder some of these efforts.…”
Section: Target Characterizationmentioning
confidence: 99%